Policy implementation of direct cash assistance program as an effort to handle Covid-19 in Dukuh village, Cikupa District, Tangerang District - Mela Mela; Ilham Aji Pangestu; Imam Rahmaddani (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The reason for this study are to decide the Execution of Direct Money Help with Taking care of Coronavirus in Dukuh Village, Cikupa Locale, Tangerang Rule and to decide the hindering and supporting elements in carrying out the dissemination of the Immediate Money Help (BLT) program in Dukuh Town, Cikupa Area, Tangerang Regime. This examination is a juridical experimental legitimate exploration that is distinct in nature, the information sources in this examination incorporate essential information and optional information. Information assortment strategies were completed by meetings and perceptions, the research location was carried out at the Dukuh Village Office, Cikupa District, Tangerang Regency. The data management technique is done by editing, categorization, and information examination. The outcomes showed that first, the Dukuh Village Government, Cikupa District, Tangerang Regency, in this case the village head and his apparatus, had carried out the Direct Cash Assistance (BLT) program allocated to the Dukuh Village community. comply with the policy requirements for prospective recipients of BLT funds. The first supporting factor is the legal structure, namely the village government which has carried out its duties and functions in accordance with applicable legal provisions. Second, the factor of legal substance, in this case is the 2020 regulation No. 6 of the village minister regarding the priority use of village funds  that has accommodated BLT to the community.